The American Literature Scholar in the Digital Age. - Earhart, Amy E.; Jewell, Andrew (Ann Arbor : University of Michigan Press, 2010)
Essays reflecting on the development of the first wave of digital American literature scholarship.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books